BSEA: A Blind Sealed-Bid E-Auction Scheme for E-Commerce Applications - Rohit Kumar Das; Sanjeet Kumar Nayak; Sourav Kumar Bhoi; Suman Kumar Choudhury; Banshidhar Majhi; Sujata Mohanty (Computers, 2016)
Due to an increase in the number of internet users, electronic commerce has grown significantly during the last decade. Electronic auction (e-auction) is one of the famous e-commerce applications. Even so, security and robustness of e-auction schemes still remain a challenge. Requirements like anonymity and privacy of the b i d value are under threat from the attackers. Any auction protocol must not leak the anonymity and the privacy of the b i d value of an honest Bidder. Keeping these requirements in mind, we have firstly proposed a controlled traceable blind signature scheme (CTBSS) because e-auction schemes should be able to trace the Bidders. Using CTBSS, a blind sealed-bid electronic auction scheme is proposed (BSEA). We have incorporated the notion of blind signature to e-auction schemes. Moreover, both the schemes are based upon elliptic curve cryptography (ECC), which provides a similar level of security with a comparatively smaller key size than the discrete logarithm problem (DLP) based e-auction protocols. The analysis shows that BSEA fulfills all the requirements of e-auction protocol, and the total computation overhead is lower than the existing schemes.